2020
DOI: 10.21203/rs.3.rs-15450/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aid for Trade flows and Recipient-Countries' Integration into the World Market for Services Exports: Do Merchandises Exports and Foreign Direct Investment Inflows matter?

Abstract: An important literature on the recipient-countries' export performance effect of Aid for Trade (AfT) flows has focused on the goods side. The few existing studies on the services exports effects of AfT interventions have reached mixed results, reflecting a positive or weak effect. The present study aims to complement these few studies by examining the effect of AfT flows on recipient-countries' share of services exports in the world services exports ('services export integration'), including through two main c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 13 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…AfT for economic infrastructure has been observed to have the dominant beneficial impact on export growth (Calì and te Velde, 2011; Vijil and Wagner, 2012), overall employment diversification (Gnangnon, 2018d), female employment enhancement Gnangnon, 2018a) and merchandise exports (Hoekman and Shingal, 2020; and Gnangnon and Ramirez, 2020). On the other hand, AfT for trade policy and regulations has also been found to have a significant impact in reducing services trade (Martínez-Zarzoso et al , 2017; Hoekman and Shingal, 2020; Gnangnon and Ramirez, 2020). Kim (2019) and Gnangnon (2018a) have suggested that the AfT for trade policy and regulations produces the most significant positive effect on export diversification and female employment growth, respectively.…”
Section: Discussion and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…AfT for economic infrastructure has been observed to have the dominant beneficial impact on export growth (Calì and te Velde, 2011; Vijil and Wagner, 2012), overall employment diversification (Gnangnon, 2018d), female employment enhancement Gnangnon, 2018a) and merchandise exports (Hoekman and Shingal, 2020; and Gnangnon and Ramirez, 2020). On the other hand, AfT for trade policy and regulations has also been found to have a significant impact in reducing services trade (Martínez-Zarzoso et al , 2017; Hoekman and Shingal, 2020; Gnangnon and Ramirez, 2020). Kim (2019) and Gnangnon (2018a) have suggested that the AfT for trade policy and regulations produces the most significant positive effect on export diversification and female employment growth, respectively.…”
Section: Discussion and Findingsmentioning
confidence: 99%
“…While the majority of previously conducted analyses have focused on exploring the effectiveness of AfT on trade costs and commodity exports, extremely few studies (Martínez-Zarzoso et al , 2017; Hoekman and Shingal, 2020; Gnangnon and Ramirez, 2020) have looked at its impact in respect to services trade. Martínez-Zarzoso et al (2017) analysed the model proposed by Calì and te Velde (2011) using panel quantile regression.…”
Section: Aid For Trade Effectivenessmentioning
confidence: 99%
“…The launch of this initiative has led to numerous studies on the effectiveness 3 of AfT flows in the economies of recipient countries. AfT effectiveness has largely been assessed with respect to recipient countries' trade performance, notably export performance where the latter has been measured by the exports of goods and services (or exports of goods, including manufacturing and primary goods) in constant prices or as a share of the Gross Domestic Product (GDP) (e.g., Bearce, Finkel, Pérez‐Liñán, Rodríguez‐Zepeda, & Surzhko‐Harned, 2013; Busse, Hoekstra, & Königer, 2012; Calì & TeVelde, 2011; Gnangnon, 2019a; Ghimire, Mukherjee, & Alvi, 2013, 2016; Helble, Mann, & Wilson, 2012; Gnangnon & Ramirez‐Ramirez, 2020; Hoekman & Shingal, 2020;Hühne, Meyer, & Nunnenkamp, 2014a, 2014b;Hynes & Holden, 2016; Martinez‐Zarzoso, Nowak‐Lehmann, & Rehwald, 2017; Te Velde & Razzaque, 2013;Vijil & Wagner, 2012). The effectiveness of AfT flows has also been evaluated with respect to several macroeconomic indicators in recipient countries.…”
Section: Introductionmentioning
confidence: 99%
“…These include trade policy and tariff policy volatility (e.g., Gnangnon, 2018; Gnangnon, 2019b; Hoekstra & Koopmann, 2012), export product diversification/economic complexity (e.g., Gnangnon, 2019c, 2019d; Kim, 2019), reduction of the digital divide (e.g., Gnangnon, 2019e); whether the launch of the AfT initiative have genuinely increased resource flows (e.g., Gnangnon, 2019f); submission of trademarks applications (e.g., Gnangnon, 2019g); employment promotion (e.g., Gnangnon, 2019h) and employment diversification (e.g., Gnangnon, 2019i); trade tax revenue (e.g., Gnangnon, 2016); and FDI inflows (e.g., Lee & Ries, 2016; Ly‐My & Lee, 2019). To the best of our knowledge, among those studies, in particular the ones that have looked at the effect of AfT on recipient countries' trade performance, only four studies (Ghimire et al, 2013; Gnangnon & Ramirez‐Ramirez, 2020; Hoekman & Shingal, 2020; Martinez‐Zarzoso et al, 2017). Ghimire et al (2013) have shown that sectoral AfT flows are positively associated with relevant sectoral exports, that is, AfT for the services sector has been associated with higher services exports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation